Geochemistry someof heavy elements in rocks, sediments, and soils of Jableh sheet 1: 50,000 / Syria / and their environmental impact - إبراهيم, أحلام; المصري, محمد سعيد; غدير , عفراء (Latakia University Journal -Basic Sciences Series, 2022)
This research focuses on determining the concentration of some heavy elements (lead, zinc, copper, and cadmium) in different types of rocks, soils, and sediments in geological sheet of Jableh. The mineralogical content was determined using the X-ray diffraction technies (XRD), and the concentration of the elements was determined using the wave polarograph device in the laboratories of the Syrian Atomic Energy Authority in Damascus. The results of XRD analyzes confirmed the control of calcite over most of the rock formations and sediments, followed by quartz, and varying proportions of clay mineral (Illite, kaolinite, montmorillonite), and some zeolitic phases (natrolyte, jesmondine, phyllibsite) appeared in sediments and soils. The results of Polarograph showed a decrease in cadmium concentration, due to the decrease in cadmium concentration in the source rocks in the study area, while the concentration of zinc, copper, and lead varied according to the different mineralogical composition of the samples, where the concentration of elements increases with the increase of clay and zeolitic minerals. Pollution indicators indicated the presence of moderate pollution with zinc and copper in some samples. This pollution is due to human and industrial activities in the study area, and it is not related to geological processes only.